STRATEGI PEMASARAN SEDUHAN DAUN BELIMBING: Studi kasus di P4S Sari Luhur - Prihadianti, Yasti; Kurniastuti, Tri (grafting, 2024)
The marketing strategy is the most important component in marketing the decoction of star fruit leaves which is a new innovative product. This study aims to: Know the marketing strategy for Carambola Leaf steeping products and Know the supporting factors and inhibiting factors in marketing Carambola leaf steeping. This research design uses Qualitative Method. Data was collected through in-depth interviews, observation and documentation. Determination of the sample using purposive sampling technique and obtained as many as 28 respondents consisting of producers and consumers. Data analysis used descriptive analysis techniques and SWOT analysis. The results of the SWOT analysis found that there were 4 strategic points that needed to be carried out, namely: Increasing the selection of quality raw materials and quality tea, Adding partnerships with Karangsari government agencies and also industry parties related to the marketing of starfruit leaf infusion, Increasing training to HR, Adding production variants according to people's tastes.